1998
DOI: 10.1177/1045389x9800901001
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Fiber Bragg Grating Sensors for Industrial Composite Cure Monitoring

Abstract: An embedded Fiber Bragg Grating (FBG) strain sensor and an FBG temperature sensor have been shown to be able to accurately monitor the industrial composite cure process of a glass/ epoxy plate devoted to aeronautical applications. The internal absolute strain level in the plate was determined, free of temperature effect thanks to a differential method. After curing, a residual compression strain of about -0.22% was observed, which represents a short part of the range in compression for a single mode fiber. Lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 2 publications
0
32
0
1
Order By: Relevance
“…The fiber optic sensor technology most widely used for structural health monitoring is fiber Bragg grating sensing [5]. However, the cross-sensitivity between temperature and strain is a serious disadvantage for many real-life applications.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber optic sensor technology most widely used for structural health monitoring is fiber Bragg grating sensing [5]. However, the cross-sensitivity between temperature and strain is a serious disadvantage for many real-life applications.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of fiber Bragg gratings (FBGs) over other optic sensor schemes are its low cost, good linearity, wavelength multiplexing capacity, resistance in harsh environments and transduction mechanism which eliminates the need for referencing as in interferometric sensors [1][2][3][4][5]. FBG sensor technology is now on the verge of maturity after almost three decades of active research and development in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The Fiber Bragg grating (FBG) sensor, due to its high sensitivity, resistance to electromagnetic interference, good durability, low cost, and more importantly capability of real-time monitoring, has become a widely accepted sensing alternative for strain [27][28][29], temperature [29][30][31], and possibly crack measurements [32,33] in civil engineering fields. Studies of using FBG sensors in crack detection on concrete and metallic structures had shown that distinguishable data alter could be observed when cracks initiated.…”
Section: Introductionmentioning
confidence: 99%